2004
DOI: 10.1101/gad.294904
|View full text |Cite
|
Sign up to set email alerts
|

Tal, a Tsg101-specific E3 ubiquitin ligase, regulates receptor endocytosis and retrovirus budding

Abstract: The tumor suppressor gene 101 (tsg101) regulates vesicular trafficking processes in yeast and mammals. We report a novel protein, Tal (Tsg101-associated ligase), whose RING finger is necessary for multiple monoubiquitylation of Tsg101. Bivalent binding of Tsg101 to a tandem tetrapeptide motif (PTAP) and to a central region of Tal is essential for Tal-mediated ubiquitylation of Tsg101. By studying endocytosis of the epidermal growth factor receptor and egress of the human immunodeficiency virus, we conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
177
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(188 citation statements)
references
References 41 publications
7
177
4
Order By: Relevance
“…Recently, it was reported that TSG101 can be monoubiquitylated by Tal, an 80-kDa RING-type E3 ubiquitin-protein ligase that contains a tandem P(S/T)AP tetrapeptide motif at its C terminus (Amit et al, 2004). Interestingly, siRNA-mediated depletion of Tal causes accelerated EGFR degradation (Amit et al, 2004), an effect that is opposite to the inhibition of EGFR degradation observed when Mahogunin is depleted (Figures 9 and 10).…”
Section: Mahogunin Functions In the Regulation Of Endosome-to-lysosommentioning
confidence: 67%
See 2 more Smart Citations
“…Recently, it was reported that TSG101 can be monoubiquitylated by Tal, an 80-kDa RING-type E3 ubiquitin-protein ligase that contains a tandem P(S/T)AP tetrapeptide motif at its C terminus (Amit et al, 2004). Interestingly, siRNA-mediated depletion of Tal causes accelerated EGFR degradation (Amit et al, 2004), an effect that is opposite to the inhibition of EGFR degradation observed when Mahogunin is depleted (Figures 9 and 10).…”
Section: Mahogunin Functions In the Regulation Of Endosome-to-lysosommentioning
confidence: 67%
“…Interestingly, siRNA-mediated depletion of Tal causes accelerated EGFR degradation (Amit et al, 2004), an effect that is opposite to the inhibition of EGFR degradation observed when Mahogunin is depleted (Figures 9 and 10). There are at least two possibilities that could explain the different effects of Mahogunin and Tal E3 ligases on EGFR trafficking.…”
Section: Mahogunin Functions In the Regulation Of Endosome-to-lysosommentioning
confidence: 91%
See 1 more Smart Citation
“…Extending this search by using PPI network analysis, we identified LRSAM1 as the only human LRR protein in the network that potentially interacted with GABARAPL2, a member of the MAP1 LC3/ATG8 family of proteins, in the core autophagy apparatus. LRSAM1, also known as Tal, has a SAM domain and a RING (E3 ubiquitin-protein ligase) domain, which mediates monoubiquitination of TSG101 at multiple sites and regulates receptor endocytosis by inactivating the ability of TSG101 to sort endocytic and exocytic (as observed with HIV-1 viral protein) cargos (32). Given this role in cargo sorting and membrane packaging of cargos, as well as the known role for bacterial ubiquitination in triggering antibacterial autophagy (33), we postulated that LRSAM1 was a plausible candidate to operate within the anti-Salmonella autophagy pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LRSAM1 is an E3 ubiquitin ligase that mediates ubiquitination of the product of the tumor susceptibility gene 101 (TSG101) at multiple sites. Previous reports indicated that TSG101 was involved in the development of multi-drug resistance in gastric cancer and was downregulated by TSG101 siRNA to reverse this effect (20,21). Our study suggests that in A549/CDDP cells, changes in the expression level of LRSAM1 could initiate changes in the monoubiquitination process of the product of TSG101.…”
Section: Discussionmentioning
confidence: 64%